2013
DOI: 10.1111/j.2041-1626.2013.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Palatal rugae and their role in forensic odontology

Abstract: Establishing a person's identity can be a difficult task in cases of traffic accidents or in mass disaster situations. The records collected to identify a decedent should be accurate and totally inclusive of objective findings. When a victim has no teeth, information for use in personal identification based on methods available in forensic odontology is much more limited than in the case of dentate victims. Palatal rugae have been considered relevant for human identification due to its stability, which is equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 32 publications
0
24
0
4
Order By: Relevance
“…Kapli et al [12] and Jain et al [9] reported that rugae growth during palatal development throughout childhood and adolescence only resulted in a change in their length, which becomes constant after adolescence. Therefore, data obtained before adolescence may contain growth-related errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kapli et al [12] and Jain et al [9] reported that rugae growth during palatal development throughout childhood and adolescence only resulted in a change in their length, which becomes constant after adolescence. Therefore, data obtained before adolescence may contain growth-related errors.…”
Section: Discussionmentioning
confidence: 99%
“…Palatal rugae are highly individualistic with respect to the combined patterns, number, shape, unification, length, width, prominence and orientation [9] and could be used as a personal print [10]. The first scientist that used palatal rugae in identification was Allen in 1889 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thomas [4] studied the histologic features of rugae cores from human embryos aged over 20 weeks and found that the reticulin fiber content was miniscule; moreover, the fibroblasts differed from those in adjacent palatal tissues only in size and amount. The palatal rugae can be used to identify a dead body because of their specificity and stability [5]. Moreover, the palatal rugae can be used as an alternative method when individual identification based on fingerprints or dental records is difficult, or when postmortem dental identification is impossible, as in cases with edentulous mouths [6].…”
mentioning
confidence: 99%
“…Palatoscopy or palate rugoscopy is the name given to the study of palatal rugae in order to establish a person's identity. [ 1 2 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%